2022
DOI: 10.3389/fpsyg.2021.787558
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Correlates of Loss of Control Eating in a Nonclinical Sample

Abstract: ObjectiveLoss of control (LOC) eating has been directly related to the core aspects of the psychopathology of eating disorders and to different dimensions of emotion and behavior regulation and self-criticism. This study investigates a model representing the interplay between these dimensions to understand LOC eating among a nonclinical sample.MethodsA total of 341 participants, recruited in a college campus (mean age 23.21, SD = 6.02), completed a set of self-report measures assessing LOC eating, weight suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…In contrast, other studies have suggested that dietary restraint is involved in the development of BED (restraint model) [44][45][46][47], while others have implied that sBED, and possibly BED, originate in long-term hypercaloric food consumption [35]. The literature supporting the former is rather mixed, and results might depend on the evaluated outcome (i.e., bulimia nervosa, BED or sBED), the sample characteristics (i.e., subjects with obesity vs. community samples), the variables studied (i.e., fasting, low-calory diets, regularity of meals), and the evaluation of other concomitant factors (i.e., dieting due to internal motivations related to body dissatisfaction vs. other reasons for dieting) [44][45][46][47][48][49][50]. Once BED is established, however, regular eating and no skipping of meals are two of the most important factors to overcome the disorder [49].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, other studies have suggested that dietary restraint is involved in the development of BED (restraint model) [44][45][46][47], while others have implied that sBED, and possibly BED, originate in long-term hypercaloric food consumption [35]. The literature supporting the former is rather mixed, and results might depend on the evaluated outcome (i.e., bulimia nervosa, BED or sBED), the sample characteristics (i.e., subjects with obesity vs. community samples), the variables studied (i.e., fasting, low-calory diets, regularity of meals), and the evaluation of other concomitant factors (i.e., dieting due to internal motivations related to body dissatisfaction vs. other reasons for dieting) [44][45][46][47][48][49][50]. Once BED is established, however, regular eating and no skipping of meals are two of the most important factors to overcome the disorder [49].…”
Section: Introductionmentioning
confidence: 99%
“…With this in mind, Tatham et al (2015) developed a brief measure covering core EDs attitudes (10 items) and behaviors (5 items) over the past week, the Eating Disorder‐15 (ED‐15). Despite being developed to assess early response to treatment, its use in nonclinical (Barbeau et al, 2022; Conceição et al, 2022; Rodrigues et al, 2022) and clinical research (Hibbs et al, 2021; Toro et al, 2022; Wade et al, 2021) has increased over the past years.…”
Section: Introductionmentioning
confidence: 99%